Electromyography for Teleoperated Tasks in Weightlessness - Hagengruber, Annette; Leipscher, Ulrike; Eskofier, Björn; Vogel, Jorn (IEEE Transactions on Human-Machine Systems, 2021)
The cooperation between robots and astronauts will become a core element of future space missions. This is accompanied by the demand for suitable input devices. An interface based on electromyography (EMG) represents a small, light, and wearable device to generate a continuous three-dimensional (3D) control signal from voluntarily muscle activation of the operator’s arm. We analyzed the influence of microgravity on task performance during a two-dimensional (2D) task on a screen. Six subjects performed aiming and tracking tasks in parabolic flights. Three different levels of fixation—fixed feet using foot straps, semi-free by using a foot rail, and free-floating feet—are tested to investigate how much user fixation is required to operate via the interface. The user study showed that weightlessness affects the usage of the interface only to a small extent. Success rates between 89% and 96% are reached within all conditions during microgravity. A significant effect between 0 and 1G could not be identified for the test series of fixed and semi-free feet, while free-floating feet showed significantly worse results in fine and gross motion times in 0G compared to ground tests (with success rates of 92% for 0G and 99% for 1G). Further adaptation to the altered proprioception may be needed here. Hence, foot rails as already mounted in the International Space Station (ISS) would be sufficient to use the interface in weightlessness. Low impact of microgravity, high success rates, and an easy handling of the system, indicates a high potential of an EMG-based interface for teleoperation in space.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Aerospace electronics; Electromyography; Electromyography (EMG); human machine interfaces; Muscles; robotcontrol; Robots; space application; Space missions; Task analysis; teleoperation; Training; weightlessness